Clinical Observation on Bu Yang Tong Luo Tang in Treating Acute Ischemic Stroke with Qi Deficiency, Blood Deficiency and Wind Syndrome - Yi, Liu; Hai, Lin (Journal of Contemporary Medical Practice, 2025)
Objective: Clinical observation of Bu Yang Tong Lue Decoction in treating acute ischemic stroke with qi deficiency, blood stasis, and wind syndrome. Methods: From January to December 2024, 60 hospitalized patients diagnosed with acute ischemic stroke with qi deficiency, blood stasis, and wind syndrome were enrolled in the Neurology Department of Xi'an Traditional Chinese Medicine Hospital. The study included 30 control group patients and 30 treatment group patients. The control group received conventional Western medical treatment, while the treatment group received Bu Yang Tong Lue Decoction with modifications. Treatment duration was 2 weeks. During this period, we observed and recorded TCM syndrome scores, neurological deficits severity scores, daily living activity ability, and modified Rankin scores before and after treatment, along with safety indicators and adverse reactions. Results: Through rank sum test, significant differences (P<0.05) were observed in NIHSS scores, BI scale scores, mRs scores, and TCM syndrome scores between the treatment group and control group before and after treatment, with post-treatment improvement compared to pre-treatment. In overall efficacy observation, the treatment group demonstrated better Western medical outcomes and TCM efficacy compared to the control group. Conclusion: Bu Yang Tong Lue Decoction is an effective medication for treating acute ischemic stroke with qi deficiency, blood stasis, and wind syndrome. It can effectively improve clinical symptoms in patients during the acute phase of ischemic stroke, enhance quality of life, and does not increase the risk of adverse reactions, making it worthy of promotion and application.